Establishment of dose-response curves for dicentrics premature chromosome condensation for radiological emergency preparedness in thailand - Benchawan Rungsimaphorn (2018)
© 2016 Genome Integrity | Published by Wolters Kluwer - Medknow. The in vitro dose calibration curves using conventional biological dosimetry - dicentric chromosome assay (DCA) and premature chromosome condensation (PCC) assay - were performed for the first time in Thailand for reconstruction of radiation dose in the exposed individuals. The peripheral blood lymphocyte samples from healthy donors were irradiated with137Cs source at a dose rate of 0.652 Gy/min to doses of 0.1, 0.25, 0.5, 0.75, 1, 2, 3, 4, and 5 Gy for DCA technique, and 5, 10, 15, 20, and 25 Gy for PCC technique. The blood samples were cultured and processed following the standard procedure as prescribed in the International Atomic Energy Agency report with slight modifications. The yield of dicentrics with dose from at least 1000 metaphases or 100 dicentrics was fitted to a linear quadratic model using Chromosome Aberration Calculation Software (CABAS, version 2.0) whereas those of PCC rings with dose from 100 rings was fitted to a linear quadratic equation at doses from 0 to 15 Gy. These curves will be useful for in vitro dose reconstruction and can support the preparedness for overexposure to radiation among public or occupational workers and eventual radiological accident in Thailand.